Analysis of Pesticide Residue in Mango by RBPR Technique in Dhangadhi, Kailali - Joshi, Manoj; Kathayat , Jang Bahadur (AMC Journal (Dhangadhi), 2026)
Mango is one of the most abundant and economically valued fruits of Nepal and is widely treated with organophosphate and carbamate insecticides for quality and pest control. But in its non-scientific use and bulk applications, toxic residues are created that affect human health as well as the environment. Mango fruits used for this investigation were bought from four major bazaars Haatbazar, Purano Sabjimandi, Chatakpur Haatbazar, and Bhat-Bhateni and analyzed for quality through RBPR process, a pesticide residue screening system technology derived from AChE enzyme inhibition. The main objective of this study is to find the existence of pesticide residues in mango fruits sold in local markets of Dhangadhi Sub-Metropolitan City, Kailali, through the Rapid Bioassay of Pesticide Residue (RBPR) method. RBPR method was used because it is easy, cheap, and convenient to use, hence particularly ideal for developing countries like Nepal where access to advanced laboratory equipment might not be readily available. Spectrophotometric detection showed variation in residues with the highest inhibition at Chatakpur Haatbazar (17.514% carbamate, 12.123% organophosphate) and lowest at Bhat-Bhateni. All were below the 35% inhibition national safety limit and hence safe for consumption. Variability in residues on markets reflects variability in post-harvest and pesticide treatment. It requires vigilant monitoring, mass consciousness, training for farmers, and adoption of safer agricultural technologies like Integrated Pest Management (IPM). The study concludes that RBPR is an affordable, cost-saving, and practical approach for local food safety assessment and must be implemented at the national level policy for making Nepalese fruit production exportable and sustainable.